Titanium superoxide: a heterogeneous catalyst for anti-Markovnikov aminobromination of olefins - Shaikh, Tanveer Mahamadali; Karabal, Pratibha U.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2009)
A new facile procedure for the aminobromination of olefins in high yields has been described using p-toluene sulfonamide (p-TsNH(2)) and N-bromosuccinimide (NBS) as introgen and bromine sources, respectively, and titanium superoxide as a truly heterogeneous catalyst. The formation of anti-Markovnikov product exclusively in all the cases studied possibly proceeding I free radical reaction pathway is remarkable. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: anti-Markovnikov addition; Bromoamination; N-Bromosuccinimide; p-Toluenesulfonamide; Titanium superoxide